Community commitment in special districts - Berman, Evan M. (2014)
Special districts now constitute about 40% of all U.S. jurisdictions, yet little is known about them. Some critics are concerned that special districts and their staffs have insufficient community commitment. This study, based on a national survey of senior managers in large special districts, examines activities and programs of special district managers that foster community building and engagement, including correlates of these. Study results reveal that special districts are committed to their communities and several strategies and conditions are associated with increased community commitment, such as jobs that focus on community interactions, service type, and ethics management, as well as, to lesser extent, graduate degree qualifications and charters that specify the role of managers in promoting the public interest and in relation to the board.